Development of the PsAQoL: a quality of life instrument specific to psoriatic arthritis - McKenna, S (2004)
Background: Patient reported outcome measures used in studies of psoriatic arthritis (PsA) have been found to be inadequate for determining the impact of the disease from the patient's perspective. Objective: To produce the PsAQoL, a PsA-specific quality of life (QoL) instrument, employing the needs based model of QoL that would be relevant and acceptable to respondents, valid, and reliable. Methods: Content was derived from qualitative interviews conducted with patients with PsA. Face and content validity were assessed by field test interviews with a new sample of patients with PsA. A postal survey was conducted to improve the scaling properties of the new measure. Finally, a test-retest postal survey was used to identify the final measure and to test its scaling properties, reliability, internal consistency, and validity. Results: Analysis of the qualitative interview transcripts identified a 51 item questionnaire. Field test interviews confirmed the acceptability and relevance of the measure. Analysis of data from the first postal survey (n = 94) reduced the questionnaire to 35 items. Rasch analysis of data from the test-retest survey (n = 286) identified a 20 item version of the PsAQoL with good item fit. This version had excellent internal consistency (α = 0.91), test-retest reliability (0.89), and validity. Conclusions: The PsAQoL is a valuable tool for assessing the impact of interventions for PsA in clinical studies and trials. It is well accepted by patients, taking about three minutes to complete, is easy to administer, and has excellent scaling and psychometric properties.